Use of Stiripentol in Patients with Dravet Syndrome: Common Practice Among Experts in Spain - Juan José García-Peñas; Rocío Calvo-Medina; Adrián García-Ron; Antonio Gil-Nagel; Vicente Villanueva; Rocío Sánchez-Carpintero (Neurology and Therapy)
Abstract Background Despite considerable evidence for the efficacy and safety of stiripentol in Dravet syndrome (DS), some aspects of stiripentol use remain challenging in clinical practice, such as dose titration and the adjustment of concomitant antiseizure medications (ASMs) to prevent potential adverse effects. Aim To (1) provide practical recommendations on the initiation of stiripentol treatment in patients with DS, (2) evaluate its effectiveness in the patient, and (3) guide the management of drug interactions and other aspects of treatment monitoring. Methods Six Spanish neurologists (the authors) with expertise in the management of pediatric and adult patients with DS held a meeting in early 2024 to develop expert recommendations regarding the use of stiripentol in DS, based on a review of the literature and their common clinical experience. Results According to these recommendations, stiripentol can be administered to patients with DS of any age, although its initiation and titration vary according to age group. Individualized adjustment of concomitant ASMs, such as valproic acid and clobazam or drugs specifically for DS (i.e., fenfluramine), at initiation and during stiripentol treatment, can mitigate drug interactions, thereby increasing the long-term tolerability of stiripentol treatment. In specific cases, stiripentol doses of > 50 mg/kg/day may be contemplated, and acute stiripentol administration may be considered to control refractory status epilepticus. Blood tests should be performed before starting stiripentol, at 3, 6, and 12 months after starting treatment, and then annually, except in the event of adverse effects, when additional testing may be necessary. Most adverse effects can be adequately managed by adjusting concomitant medications. Conclusion These practical recommendations may be easily adapted for use in different countries, and should increase physicians’ confidence in the initiation and monitoring of stiripentol treatment, thus facilitating effective management of patients with DS and improving clinical outcomes.